2012
DOI: 10.1074/jbc.m111.306183
|View full text |Cite
|
Sign up to set email alerts
|

DHHC5 Protein Palmitoylates Flotillin-2 and Is Rapidly Degraded on Induction of Neuronal Differentiation in Cultured Cells

Abstract: Background:The substrates and regulation of DHHC protein palmitoyl acyltransferases (PATs) are largely unknown. Results: Flotillin-2 palmitoylation is abolished in DHHC5 gene-targeted neural stem cells, and neuronal differentiation induces DHHC5 turnover. Conclusion: Flotillin-2 is a substrate for DHHC5, which is regulated at the protein level. Significance: The paper describes an approach to PAT substrate identification and a new PAT regulation mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
178
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(182 citation statements)
references
References 55 publications
4
178
0
Order By: Relevance
“…Similarly, the heterogeneity of RGR values that we observed could correspond to domains of 100 nm or less. Consistent with these observations, single particle tracking experiments performed on Arabidopsis roots to study the dynamics of the PM intrinsic protein PIP2;1 have revealed that about 20% of PIP2;1 fused to GFP exhibited a confined diffusion, with an average confinement range of about 90 nm (Li et al, 2012).…”
Section: Cryptogein Induces a Spatial Rearrangement Of The Pm Order Lsupporting
confidence: 51%
See 3 more Smart Citations
“…Similarly, the heterogeneity of RGR values that we observed could correspond to domains of 100 nm or less. Consistent with these observations, single particle tracking experiments performed on Arabidopsis roots to study the dynamics of the PM intrinsic protein PIP2;1 have revealed that about 20% of PIP2;1 fused to GFP exhibited a confined diffusion, with an average confinement range of about 90 nm (Li et al, 2012).…”
Section: Cryptogein Induces a Spatial Rearrangement Of The Pm Order Lsupporting
confidence: 51%
“…The depletion of membrane sterols induced by MbCD was observed to result in a disruption to the clustered organization of the protein remorin (Raffaele et al, 2009), indicating the sterol-dependent confinement of this protein into domains of 100 nm. Accordingly, both the clustering in domains of remorin and PIP2;1 were dramatically affected by treatment with cyclodextrin (Raffaele et al, 2009;Li et al, 2012), indicating a major role for sterols in the spatial segregation of these proteins in membrane domains. This treatment also induced an overall increase in acyl chain disorder and a reduction in liquid phase heterogeneity of isolated tobacco PM (Roche et al, 2008), in line with the ability of phytosterols to induce a Lo phase in ternary mixtures of lipids (Beck et al, 2007).…”
Section: Spatial Distribution and Dynamic Of Pm Heterogeneitymentioning
confidence: 93%
See 2 more Smart Citations
“…N-myristoylation is an irreversible acylation reaction at an N-terminal glycine residue, which is catalyzed by the enzyme Nmyristoyl transferase (51). S-palmitoylation is a reversible reaction, in which the acyl group is transferred to cysteine residues by palmitoyl acyltransferases, referred to as the DHHC family (52,53). In some proteins, e.g.…”
Section: Modifications Oligomerization and Trafficking Of Flotillinsmentioning
confidence: 99%